The Influence Of Work Culture, Emotional Intelligence, Individual Characteristics And Career Development On State Mts Teacher Performance In The Deli Serdang District - Pasaribu, Mansyur Hidayat; Santoso, Didik; Wijaya, Candra (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
There is a gap between the expected performance and the current performance of state MTs teachers in Deli Serdang Regency. If this problem does not receive serious attention and is not addressed immediately, the consequences will affect efforts in the field of education and are the main source for decreasing the quality of graduates. This study uses the explanatory correlational method because it aims to describe and measure the degree of relationship between variables in causal modeling using path analysis. Tests were carried out using SMART PLS to obtain the results of the most dominant indicators of the variables studied. The results showed that work culture has a positive effect on teacher performance with a path coefficient value of 0.171 (original sample column) and is significant with a P-value of 0.033 <0.05 (accepted hypotheses). Work culture has a positive effect on career development with a path coefficient value of 0.275 (original sample column) and is significant with a P-value of 0.009 <0.05 (accepted hypotheses). Individual characteristics have a positive effect on teacher performance with a path coefficient value of 0.282 (original sample column) and are significant with a P-value of 0.012 <0.05 (accepted hypothesis). Individual characteristics have a positive effect on career development with a path coefficient value of 0.399 (original sample column) and are significant with a P-value of 0.001 <0.05 (accepted hypothesis). Emotional intelligence has a positive effect on teacher performance with a path coefficient value of 0.138 (original sample column) and is significant with a P-value of 0.037 <0.05 (accepted hypothesis). Emotional intelligence has a positive effect on career development with a path coefficient value of 0.227 (original sample column) and is significant with a P-value of 0.028 <0.05 (accepted hypothesis). Career development has a positive effect on teacher performance with a path coefficient value of 0.371 (original sample column) and is significant with a P-value of 0.001 <0.05 (accepted hypotheses).